Crack-healing and pre-oxidation behavior of ZrO2 fiber toughened ZrB2-based ceramics. (January 2015) - Lin, Jia; Huang, Yu; Zhang, Houan
Abstract: Structural ceramics, including zirconium diborides, are brittle and sensitive to superficial flaws such as cracks and pores. These aspects, which can lead to unexpected catastrophic failure, are still the obstacles preventing the structural ceramics from being widely used. In this paper, a ZrB2 ceramic composite reinforced with SiC particles and ZrO2 fibers was prepared. The oxidation behavior and crack-healing ability of the ZrO2 fiber toughened ZrB2 -based ceramics as a function of temperature and time were investigated. The results here indicate that the strength of the ZrO2 fiber toughened ZrB2 -based ceramics was recovered to 1130 ± 32 MPa at the temperature of 1200 °C for 30 min, which was ~ 44 MPa higher than that of polished specimens, and the fracture toughness was also recovered to 6.92 ± 0.05 MPa·m 1/2 . The crack was completely healed with oxidation products consisting ZrO2 and SiO2 . The good crack-healing ability of the ZrO2 fiber toughened ZrB2 -based ceramics would make this composite highly useful as it could heal defects and flaws autonomously in practical applications. Highlights: Crack healing behavior of ZrO2 fiber toughened ZrB2 based ceramics was investigated. The crack was healed at temperature ranging from 800 to 1200 °C. The strength was recovered to 1130 ± 32 MPa at the temperature of 1200 °C for 30 min.